Effectivity of Exoskeleton Robot-Assisted Therapy on Improving Muscle Strength in Post-Stroke Patient - Aulia Salwa Alfaina; Rahmi Isma Asmara Putri; Hari Peni Julianti; Trianggoro Budisulistyo; Rifky Ismail (RSUP Dr. Kariadi, 2021)
Background: Upper limb weakness is the most disability caused by stroke. The availability of physiotherapists is still limited in Indonesia. The exoskeleton robot is a developing technology that involve in stroke rehabilitation therapy. Objective: To evaluate the effectiveness of exoskeleton robot-assisted therapy on improving muscle strength of patients after stroke. Methods: An experimental study with two groups pre-test and post-test design carried out using consecutive sampling among outpatient stroke patients in Diponegoro National Hospital (RSND) and William Booth Hospital (RSWB), Semarang. Patients in the robotic group (RG) (n=8) received 16 training sessions. Each session consists of 30 passive and ten active-weighted elbow flexion-extension with the exoskeleton robot. Meanwhile, the control group (CG) (n=8) received equivalent training of conventional therapy. The primary outcome of muscle strength was measured by Manual Muscle Testing (MMT) and handheld dynamometer. Pre and post-test MMT score data in each group were analyzed by Wilcoxon test, while handheld dynamometer score data were analyzed by paired t-test. Data between the two groups were analyzed by Mann-Whitney test and unpaired t-test. Results: Significant improvements were shown for the MMT score (RG: p=0.014, CG: p=0.034). There were significant handheld dynamometer score improvements on muscle strength for elbow flexor and extensor in RG (p = 0.008 and p = 0.005 respectively) and in CG (p=0.036 and p=0.008 respectively). No significant differences for MMT and handheld dynamometer score between the two groups. Conclusion: The exoskeleton robot-assisted therapy was as effective as conventional therapy for improving muscle strength in stroke patients.